PENGARUH TERAPI NAFAS DALAM TERHADAP PENURUNAN HIPERTENSI DI UPT PSLU JOMBANG: PENGARUH TERAPI NAFAS DALAM TERHADAP PENURUNAN HIPERTENSI DI UPT PSLU JOMBANG - Bakar, Abu; Roni, Faishol; Sasmito, Nanang Bagus (LPPM STIKes Bahrul Ulum Jombang, 2017)
Hypertension is a disorder of the circulatory system and is a problem for the elderly. One easy therapy is deep breathing relaxation techniques that can calm and calm muscles. The purpose of this study was to determine the effect of breath relaxation techniques on changes in blood pressure in the elderly with hypertension. The type of research used was the pre-experimental One Group Pre-Post Test Design, the elderly who had their blood pressure measured first were then given a deep relaxation breathing technique and after giving breath relaxation techniques the elderly were re-measured their blood pressure then analyzed by comparing the mean blood pressure before and after being given deep breath relaxation techniques. The population in this study were 25 elderly with hypertension in UPT PSLU Jombang. The sampling technique used was total sampling and obtained 25 samples of elderly people with hypertension. The measuring instrument used is the observation sheet. From the results of the study, it was found that the value of blood pressure before breathing relaxation techniques in the hole was 171.00 diastole 78.00 and p = 0.00 (p = <0.05). The mean blood pressure after breathing relaxation techniques in systole was 17.36 diastole 3.20 and p = 0.172 (p => 0.05). There is an effect of blood pressure systole in the elderly before and after deep breathing relaxation techniques of 17.36 and in diastole there is no effect 3.20.